A highly efficient rod-like-CeO2-supported palladium catalyst for the oxidative carbonylation of glycerol to glycerol carbonate. Issue 28 (10th May 2021) - Wang, Ziyan; Guo, Shuo; Wang, Zhimiao; Li, Fang; Xue, Wei; Wang, Yanji
Abstract : Pd/CeO2 -r was prepared by a two-step hydrothermal-impregnation method for oxidative carbonylation of glycerol. It exhibited high activity, and glycerol conversion was 93% and glycerol carbonate selectivity was 98% with a TOF of 1240 h −1 under optimized conditions. Abstract : A rod-like-CeO2 -supported Pd catalyst (Pd/CeO2 -r) was prepared using two-step hydrothermal impregnation and used in the oxidative carbonylation of glycerol to produce glycerol carbonate. The characterization results showed that the Pd was highly dispersed on the surface of the CeO2 -r, and metallic Pd was the main species in the catalyst. The Pd/CeO2 -r exhibited good catalytic performance for the oxidative carbonylation of glycerol. Under optimized reaction conditions, the glycerol conversion and glycerol carbonate selectivity were 93% and 98%, respectively, and turnover frequency was 1240 h −1 . However, because of the leaching of Pd and the growth of Pd particles, the catalyst was gradually deactivated throughout reuse.